Evaluation of the amount of apically extruded debris using different root canal instrumentation systems (Mustansiria Dental Journal, 2018)
The purpose of this study was to evaluate the amount of apically extruded debrisusing 5 types of nickel–titanium endodontic instruments (Hand ProTaper, RotaryProTaper, Rotary Mtwo, RECIPROC and WaveOne). Seventy-five freshly extractedmandibular premolar teeth were used in this study. All teeth were shortened to alength of 14mm. The specimens were randomly divided into five groups (each groupcontaining 15 samples) according to the type of instrumentation systems used. GroupI: instrumented by hand ProTaper system (Hand technique). Group II: instrumentedby rotary ProTaper system. Group III: instrumented by rotary Mtwo system. Group1V: instrumented by single file RECIPROC system. Group V: instrumented by singlefile WaveOne system. Debris extruded from the apical foramen was collected intopre-weighed glass vials. The difference between the weights of vial (pre-weight andpost-weight) represented the weight of debris extruded from apical foramen duringcanal preparation. The results showed that all groups induced extrusion of debris,Mtwo group (III) has statistically the lowest mean value of apically extruded debris incomparing with all other groups, followed by rotary ProTaper (II), hand ProTaper (I),and WaveOne (V) groups respectively. While the RECIPROC group (IV) hasstatistically highest mean value.